PERAN MEDIA PEMBELAJARAN DALAM MENINGKATKAN MINAT BELAJAR SISWA SEKOLAH DASAR - Febby Rahmanda; Sintia Maharani (STKIP Persada Khatulistiwa Sintang, 2022)
When children enter primary education, the role of learning media in increasing interest in learning is very popular in education. There are many technologies that have been developed in the present and implemented for the first time in the world of education. Giving rewards in the use of media is also very good in the learning process. This allows the use of media to adapt to the learning on that day so as to be able to answer material problems from the media used. This makes it one of the few developed countries in the world that already uses learning media. Which, able to improve student learning in elementary school. This allows teachers to make better learning media and be able to give the best to students and show their work and creativity in making these learning media. In addition, the media does not cause boredom when learning in class and is able to increase motivation in the learning process.